The effect of leadership style on the employees’ job motivation in health care centers in Shiraz - EHSAN GOORAKI; HESAMEDDIN NOROOZI; SAADAT MARHAMATI; FARANAK BEHZADI (Journal of Advances in Medical Education and Professionalism, 2013)
Introduction: Leadership style is one of the most debated topics in management (urban health-care centers), which has influenced a great number of managers and employees. The present study aimed to determine the impact of the managers’ leadership styles on the employees’ job motivation based on the Vroom-Yetton model. Methods: This study was a descriptive–analytical one and the research environment included the managers of health-care centers in Shiraz, Iran. The study data were collected through two questionnaires which were developed by the researchers, and the statistical analyses were performed using the SPSS statistical software. Results: The findings of the study indicated that 37%, 32%, and 7% of the managers’ leadership styles were cooperative type 1, cooperative type 2, and centric, respectively. In addition, 48% and 42% of the study subjects had average and high levels of maintenance motivational needs, respectively. Besides, 54% and 41% of the employees had average and high levels of motivational needs, respectively. The results showed a significant relationship between the employees’ motivational needs and the type of service as well as age (a <0.05). A significant relationship was also found between the employees’ provocative motivational needs and the type of service; however, no significant relationship was observed between the employees’ motivational needs and the demographic variables. No significant relationship was found between the managers’ leadership style and demographic variables, either. Conclusion: Given that the majority of the mangers of the research society have the leadership style of consultative and cooperative, this matter can improve the employees’ provocative and maintenance motivational needs in health-care centers.